From Blame Culture to Learning Culture in Healthcare Services (Literature Review) - Irawati; Anjar Budi Astoro (PT FORMOSA CENDEKIA GLOBAL, 2024)
Patient safety is one of the key indicators of healthcare service quality. This study evaluates strategies for developing a safety culture in hospitals, focusing on shifting from a blame culture to a learning culture. The research employs Systematic Literature Review techniques. The findings indicate that management commitment, psychological safety, and staff engagement are critical components in fostering an effective safety culture. The study suggests the importance of continuous training and supportive reporting systems as strategies to enhance patient safety. This research contributes to a better understanding of how safety culture can be strengthened in hospital environments.